2016
DOI: 10.3233/wor-162255
|View full text |Cite
|
Sign up to set email alerts
|

Firefighting and mental health: Experiences of repeated exposure to trauma

Abstract: Results of the current study suggest that RET is a significant concern for emergency responders that warrants additional research and attention. It is likely that the long term consequences of RET are closely intertwined with other mental health outcomes and general well-being of this important occupational group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 27 publications
1
88
0
7
Order By: Relevance
“…This result may be a conservative estimate because the CAGE questionnaire may be less sensitive in women compared to men (Dhalla & Kopec, 2007). Problem drinking was significantly associated with common mental health issues in the Fire Service, such as depression, anxiety, and symptoms of PTSD (Carey et al, 2011; Fullerton, Ursano, & Wang, 2004; Guo et al, 2006; Jahnke et al, 2014; Jahnke et al, 2016). A large national formative study on alcohol use among firefighters found a strong perception that occupational stress and repeated exposure to trauma lead to excessive alcohol use as a method of coping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may be a conservative estimate because the CAGE questionnaire may be less sensitive in women compared to men (Dhalla & Kopec, 2007). Problem drinking was significantly associated with common mental health issues in the Fire Service, such as depression, anxiety, and symptoms of PTSD (Carey et al, 2011; Fullerton, Ursano, & Wang, 2004; Guo et al, 2006; Jahnke et al, 2014; Jahnke et al, 2016). A large national formative study on alcohol use among firefighters found a strong perception that occupational stress and repeated exposure to trauma lead to excessive alcohol use as a method of coping.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to determine whether women firefighters also are at risk for unhealthy levels of alcohol consumption due to its deleterious social and health effects (Bates, Bowden, & Barry, 2002; Booth & Feng, 2002; Bouchery, Harwood, Sacks, Simon, & Brewer, 2011; Breslow, Guenther, Juan, & Graubard, 2010; Caetano, 1987; Caetano & Cunradi, 2002; Caetano, Schafer, Fals-Stewart, O'Farrell, & Miller, 2003; Centers for Disease Control and Prevention, 2015; Chartier & Caetano, 2012; Cunradi, Caetano, Clark, & Schafer, 1999; Ehlers, Gilder, Criado, & Caetano, 2010; Galvan & Caetano, 2003; Greenfield, 1998; Jahnke et al, 2014; Kaplan et al, 2014; Klingemann, 2001) and association with occupationally-related risk factors, such as exposure to trauma (Jahnke, Poston, Haddock, & Murphy, 2016). This study fills the gap in the literature on women firefighters and alcohol consumption by presenting data from the first national study of the health of women in the fire service.…”
mentioning
confidence: 99%
“…All these stress-related symptoms were directly or indirectly influenced by personality traits, working conditions and maladaptive coping strategies [20][21][22][23][24][25][26]. Strictly speaking, the perpetuation of trauma exceeds exposure to potentially traumatic events, as it is also influenced by personal and occupational characteristics, organizational structure, interpersonal relationships and mental and physical health conditions [12,14,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Through this analysis, we identified the main risk and protective factors for the development of PTSD and other stress-related diseases in firefighters as being the perception of stress, social and organizational support, training and experience, usually associated with being a volunteer or professional firefighter, and the choice of coping strategies. These factors influence each other, offering evidence that stress-related diseases are the result of a set of failures that may occur before, during and after potentially traumatic events [12,14,16,27,[29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation